Micropropagation of the narrow endemic Hladnikia pastinacifolia (Apiaceae) - Ambrozic-Dolinsek, Jana; Ciringer, Terezija; Kaligaric, Mitja (Acta Botanica Croatica, 2016)
The monotypic Hladnikia pastinacifolia Rchb. is a narrow endemic species, with an extremely small distribution area in Slovenia, prone to any kind of threat that could lead to species extinction. Tissue culture techniques are proposed as a conservation measure for rapid propagation and ex-situ conservation. Tissue culture was initiated from seeds and juvenile plants obtained from natural sites on a solid Murashige and Skoog (MS) medium, with and without growth regulators. We tested various combinations and concentrations of growth regulators, and the best proliferation of axillary shoots, on average 14, was obtained on MS medium with 5 ?M BAP and 3 ?M IBA and 3% sucrose. Rooting was achieved after transferral of the shoots to an MS medium with 2 ?M IBA and 3% sucrose. The rooted plants were acclimatized on a mixture of limestone sand, potting soil and vermiculite in a ratio of 10:2:2, with pH in the range of 7.5–8.0. In vitro propagation methods provide an important opportunity for the propagation and preservation of H. pastinacifolia by rapidly increasing the number of plants, without disturbing the wild population.